EFFECT OF ARTIFICIAL INSEMINATION TIME USING LIQUID SPERM TOWARD SUCCESS PREGNANCY LEVEL THIN TAIL SHEEP - Fadli, Hasan (Jurnal Sains Peternakan, 2015)
The purpose of this study was to determine effect of artificial insemination time using liquid sperm toward success pregnancy level thin tail sheep. This research was carried out on 11 October to 11 November 2013, in Mr. Zainal Arifin animal husbandry the village of Dusun Bandar Bandar Kedungmulyo District of Jombang. The experimental design used was a completely randomized design ( CRD ) with 3 treatments and 6 replications . Treatment is given P1: 12 hours of artificial insemination after estrus signs appear; P2 : 24 hours of artificial insemination after estrus signs appear; P3 : 36 hours of artificial insemination after estrus signs appear. The results of the study were obtained P1 with insemination treatment at 12 hours after the first sign of lust has significant opportunity in comparison with P2 and P3, which is in line with research conducted Mustafa (2005 ) Artificial insemination is done 12 hours after the appearance of signs Symptoms of lust. Because ovulation occurs 24-30 hours in sheep at the commencement of lust. So the time is right for insemination is between 12-18 hours after symptoms appear lust.Keyword: Artificial Insemination, Liquid Sperm, Pregnancy Level